2018
DOI: 10.3201/eid2405.171369
|View full text |Cite
|
Sign up to set email alerts
|

Alkhurma Hemorrhagic Fever Virus RNA in Hyalomma rufipes Ticks Infesting Migratory Birds, Europe and Asia Minor

Abstract: Alkhurma hemorrhagic fever virus RNA was detected in immature Hyalomma rufipes ticks infesting northward migratory birds caught in the North Mediterranean Basin. This finding suggests a role for birds in the ecology of the Alkhurma hemorrhagic fever virus and a potential mechanism for dissemination to novel regions. Increased surveillance is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 14 publications
(18 reference statements)
1
25
0
Order By: Relevance
“…on birds migrating north through Europe (147,148). Further studies have confirmed that such ticks can be infected with zoonotic pathogens (149), such as Crimean-Congo haemorrhagic fever virus. But again, it is unlikely that such ticks will survive and thrive in the UK, so onward transmission of pathogens will be limited.…”
Section: Risks From Exotic Ticksmentioning
confidence: 93%
“…on birds migrating north through Europe (147,148). Further studies have confirmed that such ticks can be infected with zoonotic pathogens (149), such as Crimean-Congo haemorrhagic fever virus. But again, it is unlikely that such ticks will survive and thrive in the UK, so onward transmission of pathogens will be limited.…”
Section: Risks From Exotic Ticksmentioning
confidence: 93%
“…in France [40], Rhipicephalus microplus in Galápagos Islands [41] and TBVs in Hyalomma spp. ticks collected on migratory birds in Sweden [42]. Remarkably, this allowed the detection of expected pathogens (i.e.…”
Section: Tick-borne Pathogen Coinfections Revealed By Microfluidic Pcrmentioning
confidence: 96%
“…This is one of the largest bird migration systems [14], in which Capri in Italy and Antikythira in Greece are two important stopover sites for birds arriving from Africa, after crossing the Sahara Desert and the Mediterranean Sea, and were therefore used as collection points in this investigation. Previous studies have shown that northward migrating birds, utilizing stopover sites in and near the Mediterranean Sea often are infested with ticks carrying zoonotic pathogens, both bacterial and viral [15][16][17]. In this study, the role of northward migratory birds in the dispersal of tick-borne AP in the African-Western Palearctic region was investigated using molecular detection methods.…”
Section: Introductionmentioning
confidence: 99%